Time-Varying Biased Proportional Guidance with Seeker’s Field-of-View Limit - Zhe Yang; Hui Wang; Defu Lin (International Journal of Aerospace Engineering)
Traditional guidance laws with range-to-go information or time-to-go estimation may not be implemented in passive homing missiles since passive seekers cannot measure relative range directly. A time-varying biased proportional guidance law, which only uses line-of-sight (LOS) rate and look angle information, is proposed to satisfy both impact angle constraint and seeker’s field-of-view (FOV) limit. In the proposed guidance law, two time-varying bias terms are applied to divide the trajectory into initial phase and terminal phase. The initial bias is designed as a function of LOS rate and look angle to maintain the seeker’s lock-on while the final bias eliminates the deviation between the integral value of angle control bias and the expected bias amount. A switching logic is adopted to change the biases continuously so that there is no abrupt acceleration change during the engagement. Extensive simulations considering both kinematic and realistic missile models are performed to illustrate the efficiency of the proposed method.